From "Visual Imagery" to "Precise Definition": Analyzing Two Modes of Interpretive Expressions in Xu Yuanchong's English Translation of the Chu Ci (Journal of humanities and social sciences exploratio, 2026)
This study conducts a comprehensive analysis of the ideographic approach employed in Xu Yuanchong's English translation of the Chu Ci (Songs of the South). It uncovers the dual dimensions of poetics and Confucianism inherent in Xu's translation strategy. On the one hand, the poetic ideographic interpretation focuses on shaping the "form of poetry," emphasizing the rich presentation of "visual imagery," allowing the translated text to enjoy considerable freedom in expression, occasionally deviating significantly from the original meaning of Chinese characters. On the other hand, the Confucian ideographic interpretation is grounded in the precise communication of Confucian principles, striving for the "precise definition" of words and delving into etymological depths to ensure a close connection between the translation and the original meaning of Chinese characters. Within specific chapters of the Chu Ci, this dual tendency of interpretation manifests distinctively: the poetic ideographic interpretation is prevalent in the romantic expanse of Li Sao and Jiu Ge, while the Confucian ideographic interpretation bears more profound reflections in Tian Wen and Jiu Zhang. Notably, the Confucian ideographic interpretation exhibits stronger intertextuality among texts, enriching the interpretive layers of the translation through the intertwined dialogue with Confucian classics and other cultural traditions.
Keywords: Chu Ci; English translation; Xu yuanchong; Ideographic approach